Fabrique Sud-Sud de référentiels internationaux de développement - Carlos Cortés Zea; Lauren Lecuyer (Revue Internationale des Études du Développement)
Theoretical frameworks can no longer explain the new configuration of international development cooperation post-2015. With the apparent decline of traditional donors, the activism of “Southern Providers” has been upsetting the balance in the international arena. Through case studies of a Brazilian and a Mexican project, both in the field of family farming, we bring to light the historical links of these projects with national development policies. From an international relations perspective rooted in public action sociology, we question their internationalization to determine whether these countries convey new standards.